2021
DOI: 10.3390/su13084286
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Recycling of High-Strength Concrete as an Alternative to Natural Aggregates in Building Structures

Abstract: The application of recycled coarse aggregates (RCA) in high-performance concrete (HPC) was analyzed in the article. In the paper, the behavior of HPC with coarse recycled aggregate and natural coarse aggregate (NCA) was compared. Short-term experiments were conducted, including concrete deformation, deflection, load bearing capacity, and cracking of beams. The analysis involved reinforced concrete T-beams made in 100% of RCA or NCA. The studies indicated that the beams with recycled aggregate are characterized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 47 publications
(83 reference statements)
1
7
0
Order By: Relevance
“…Cracking pattern and deflection response of beams containing waste aggregate are similar to those of natural aggregate concrete beams as reported by Malešev et al 2010 [14]; Seara-Paz et al 2018 [18]; Wang et al 2019 [21]; Oad et al 2019 [4]. However, some researchers indicated that deflection is greater and cracks are more and closer in waste aggregate beams due to lower modulus of elasticity and higher shrinkage, respectively [5,11,12,17,19].…”
supporting
confidence: 74%
See 3 more Smart Citations
“…Cracking pattern and deflection response of beams containing waste aggregate are similar to those of natural aggregate concrete beams as reported by Malešev et al 2010 [14]; Seara-Paz et al 2018 [18]; Wang et al 2019 [21]; Oad et al 2019 [4]. However, some researchers indicated that deflection is greater and cracks are more and closer in waste aggregate beams due to lower modulus of elasticity and higher shrinkage, respectively [5,11,12,17,19].…”
supporting
confidence: 74%
“…On the other hand, demolition waste is increasing and has become one of the most serious concerns worldwide [1][2][3]. So, recycling waste materials in constructions offers environmental as well as economic benefits such as reducing extraction of virgin materials and overall projects costs [2,[4][5][6].Since concrete is the most common construction material and about 75 % of concrete volume is occupied by aggregate, waste materials like crushed concrete and/or crushed bricks have successfully used as coarse and/or fine aggregate in various percentages to produce new concretes even though they, generally; give lower strength and stiffness than conventional concrete [7][8][9][10][11][12]. However, studies show that less or no negative effect is observed when the ratio of waste aggregate is about 50 % or less [1,8,13].…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Wang Q et al [29] reported that one of the characteristics of the concrete that was investigated in this examination is autogenous shrinkage, as the results proved that it is possible to reduce shrinkage by using recycled aggregates, as the researchers studied many ratios of aggregate with different ratios of (w/c). Sadowska B. and Małgorzata G. 's [30] study demonstrates that substituting recycled aggregate for conventional aggregate in high-performance concrete results in a loss of concrete strength, modulus of elasticity, and tensile resistance. Salgado F. and Silva F. [31] in this one, three types of recycled aggregate were used: construction aggregate, concrete aggregate, aggregate, and a mixture of the two types.…”
Section: Introductionmentioning
confidence: 98%